Border governance in ancient China-study between 2070 B.C.-1279 A.D. - Geliang, Liu (Sinología hispánica. China Studies Review, 2022)
This article provides a study of border governance in ancient China. It interprets the state of domination in ethnic minorities areas by the central feudal dynasty government between 2070 B.C-1279 A.D which is recognized among the relevant academic community in China. In this multi-ethnic country with a long history of feudal dynasty, many ethnic minorities live on the borders of China, thus the central feudal dynasty has faced complicated problems of simple border governance in this vast land. Although feudal dynasties in various periods of Chinese history differed in the content of border governance, their governance systems were of the same origin and were constantly improving. The author strives to interpret the border governance model at each historical stage, in order to order a clear historical context and provide a window for Spanish-speaking sociologists to understand the governance of ethnic minorities in ancient China.